Design, synthesis and evaluation of some new 4-aminopyridine derivatives in learning and memory - Sinha S.K.; Shrivastava S.K. (My University, 2025)
Some new anilide and imide derivatives of 4-aminopyridine (4AP) were synthesized and evaluated against antiamnesic, cognition enhancing and anticholinesterase activity through their respective in vitro and in vivo models. These newly synthesized derivatives have illustrated an enhanced cognition effect on elevated plus maze model and also demonstrated a significant reversal in scopolamine-induced amnesia in same model. The IC50 value of synthesized compounds showed maximum activity of 4APMb compared to standard drug donepezil and other derivatives, whereas its enzyme kinetic study revealed a non-competitive inhibition of acetycholinesterase (AChE) and a competetive inhibition of butyrylcholinesterase (BChE). Significant inhibitions in AChE activity by all the synthesized compounds were found in specific brain regions that is prefrontal cortex, hippocampus and hypothalamus. The docking study confirmed their consensual interaction with AChE, showed an affinity and binding with the key peripheral anionic site residues Trp-286, Tyr-124 and Tyr-341 of AChE. © 2013 Elsevier Ltd. All rights reserved.